Endurance performance adaptations between SSG and HIIT in soccer players: A meta-analysis - Clemente, F. M.; Moran , J.; Ramirez-Campillo, R.; Beato, M.; Afonso, J. (International Journal of Sports Medicine, 2023)
The objective of this systematic review with meta-analysis was to compare the endurance performance chronic adaptations induced by running-based high-intensity interval training (HIIT), small-sided games (SSGs), and combined HIIT+SSGs in male and female youth and adult soccer players. The studies included in this review followed the PICOS criteria: (i) healthy soccer players; (ii) interventions based on SSGs; (iii) comparators exposed to only HIIT or combined SSGs+HIIT; (iv) endurance performance variables. Studies were searched for in the following databases: (i) PubMed; (ii) Scopus; (iii) SPORTDiscus; (iv) Web of Science. After conducting an initial database search that retrieved a total of 5,389 records, a thorough screening process resulted in the inclusion of 20 articles that met the eligibility criteria. Sixteen studies reported outcomes related to endurance performance measured through field-based tests, while five studies provided results from direct measurements of maximal oxygen uptake (VO2max). Results showed a non-significant small-magnitude favoring effect for the HIIT groups compared to the SSG groups (ES=0.37, p=0.074) for endurance, while a non-significant small-magnitude favoring SSGs was observed (ES=-0.20, p=0.303) for VO2max. Despite the very low certainty of evidence, the findings suggest similar effects induced by both SSG and HIIT on improving endurance performance and VO2max.